1999
DOI: 10.1068/d170133
|View full text |Cite
|
Sign up to set email alerts
|

Selling Nature to save It? Biodiversity and Green Developmentalism

Abstract: New supranational environmental institutions, including the Convention on Biological Diversity (CBD) and the 'green' World Bank, reflect attempts to regulate international flows of 'natural capital* by means of an approach I call 'green developmentalism*. These institutions are sources of cco-dcvclopmcnt dollars and of a new 'global* discourse, a postncolibcral environmentaleconomic paradigm. By the logic of this paradigm, nature is constructed as a world currency and ecosystems arc receded as warehouses of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
274
0
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 574 publications
(293 citation statements)
references
References 12 publications
0
274
0
11
Order By: Relevance
“…Our intention is to highlight ecological and economic patterns associated with movements towards conservation banking more generally, exemplified here by USA species banking. Mitigation practices that manage environmental degradation through offsetting trades in conservation measures derive from neoliberal conservation principles (McAfee 1999;Sullivan 2006;Igoe & Brockington 2007;Büscher et al 2012). Key to this is the policy decision to solve environmental problems by creating markets for profitable exchange of measures of environmental health and damage as commodities, rather than through punishment for non-compliance or through acknowledging intrinsic value (Hahn 2000;Morris 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our intention is to highlight ecological and economic patterns associated with movements towards conservation banking more generally, exemplified here by USA species banking. Mitigation practices that manage environmental degradation through offsetting trades in conservation measures derive from neoliberal conservation principles (McAfee 1999;Sullivan 2006;Igoe & Brockington 2007;Büscher et al 2012). Key to this is the policy decision to solve environmental problems by creating markets for profitable exchange of measures of environmental health and damage as commodities, rather than through punishment for non-compliance or through acknowledging intrinsic value (Hahn 2000;Morris 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Malthus (1993Malthus ( [1798), in addition to his (in)famous embrace of famine and disease as`natural' or what he called`preventive' checks on population growth, also stated that:`i t appears, that a society constituted according to the most beautiful form that imagination can conceive, with benevolence for its moving principle, instead of self-love, and with every evil disposition in all its members corrected by reason and not force, would, from the inevitable laws of nature, and not from any original depravity of man [sic], in a very short period degenerate into a society constructed upon a plan not essentially different from that which prevails in every known state at present; I mean, a society divided into a class of proprietors, and a class of labourers, and with self-love the main-spring of the great machine'' (Malthus, 1993(Malthus, [1798, pages 64^65). There is, of course, much more to be said about green capitalism, its origins, and a proliferation of market fundamentalism in contemporary environmental policy making (see eg Goldman, 2005;Heynen et al, 2007;Krueger and Gibbs, 2007;Liverman, 2004;McAfee, 1999;Mansfield, 2004a;2004b;. But the point is that markets, more or less accurate prices, enclosures of various kinds, a faith in the choices of ostensibly independent and rational individuals, and investment of capital by innovative entrepreneurs constitute the ubiquitous tropes of green capitalism.…”
mentioning
confidence: 99%
“…We have suggested that the numbers used to account for nature in applications such as natural capital accounts and biodiversity offsetting conceptually simplify the natures thus represented, allowing their enrolment into capitalist enterprise in new ways that may also generate concern (also see McAfee, 1999;Castree, 2003;Robertson, 2006;Sullivan, 2009Sullivan, , 2013bFourcade, 2011;Pawliczek and Sullivan, 2011;Verran, 2013;Dempsey, 2015). New arithmetical ecological accounting practices format the world as measurable and potentially controllable (Boylan, 2016), as well as able to be 'valued' in the narrow economic sense of being given a monetary worth that under conditions of private ownership may potentially be(come) profitable.…”
Section: (Re)assessmentsmentioning
confidence: 99%